2010
DOI: 10.1371/journal.ppat.1001233
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Studies of Nonstructural Protein 2 of the Hepatitis C Virus Reveal Its Key Role as Organizer of Virion Assembly

Abstract: Non-structural protein 2 (NS2) plays an important role in hepatitis C virus (HCV) assembly, but neither the exact contribution of this protein to the assembly process nor its complete structure are known. In this study we used a combination of genetic, biochemical and structural methods to decipher the role of NS2 in infectious virus particle formation. A large panel of NS2 mutations targeting the N-terminal membrane binding region was generated. They were selected based on a membrane topology model that we es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
220
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(246 citation statements)
references
References 70 publications
22
220
2
2
Order By: Relevance
“…Our result that DGAT1 is a key determinant for the localization of NS5A to LDs in the absence of other viral components is in agreement with recent reports showing that the presence of other viral components (e.g. NS2 or core) modulates, but is not critical to the intracellular trafficking of NS5A (22,23). Other non-structural viral proteins implicated in viral assembly (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Our result that DGAT1 is a key determinant for the localization of NS5A to LDs in the absence of other viral components is in agreement with recent reports showing that the presence of other viral components (e.g. NS2 or core) modulates, but is not critical to the intracellular trafficking of NS5A (22,23). Other non-structural viral proteins implicated in viral assembly (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Along these lines, HCV NS2 has been shown to interact either directly or indirectly with E1, E2, p7, NS3, NS4A, NS5A, and NS5B (44)(45)(46)(47)(48). Another study revealed interactions of NS2 with E1, E2, and p7, which are mediated by the transmembrane segments of the respective proteins (49). Similar studies for pestiviruses will significantly benefit from our identified gain-of-function mutants in NS2 and NS3.…”
Section: Discussionmentioning
confidence: 71%
“…One well-characterized ion channel-independent p7 function is its interaction with NS2, targeting the latter to defined loci within infected cells where it is thought to act as a 'particle assembly scaffold' (Boson et al, 2011;Jirasko et al, 2008Jirasko et al, , 2010Ma et al, 2011;Popescu et al, 2011;Stapleford & Lindenbach, 2011;Tedbury et al, 2011). p7 and NS2 in concert control sub/genotypedependent compartmentalization of HCV core protein between the ER and lipid droplets, with more efficient particle production resulting from ER-associated core (Boson et al, 2011).…”
Section: Hcv P7mentioning
confidence: 99%
“…However, the 16 Å resolution of this structure was not sufficient to discern the precise arrangement of protomers within the channel complex, making further atomic structural information highly desirable. Early solution NMR studies yielded the structure of the genotype 1b p7 C terminus (PDB ID: 2K8J) (Saint et al, 2009), as well as an NMRguided molecular dynamics model of the complete monomer in a hairpin conformation (Montserret et al, 2010). Subsequent solid-state NMR investigations also supported a monomeric hairpin, albeit with altered helical positioning (Cook & Opella, 2010.…”
Section: Hcv P7mentioning
confidence: 99%